A complex approach in rehabilitation of the patients after the anterior cruciate ligament reconstruction - I.Ya Hrubar (Здоров’я, спорт, реабілітація, 2019)
The Purpose was to improve the treatment outcomes of patients who undergo ACL reconstruction under arthroscopic control through a comprehensive approach to their rehabilitation program. Materials and methods. We have implemented a system of comprehensive rehabilitation of patients after the ACL reconstruction under arthroscopic control, which relied on the phase of the clinical course of the postoperative period. Results. The study involved 40 patients who underwent anterior cruciate ligament reconstruction under arthroscopic control. Experimental group (20 people) who applied a comprehensive approach in rehabilitation after ACL reconstruction, taking into account the phase of the clinical course of the postoperative period. The second group was the control group (20 patients) in which rehabilitation was carried out under the existing program. The use of cryotherapy with adjustable pulse compression in patients of the experimental group from the first day allowed to reduce twice the use of non-narcotic analgesics. Analyzing the dynamics of flexion in the knee joint, it was found that patients of the experimental group on the 25th day performed flexion by 88.46% of the appropriate maximum. Whereas in the control group just - 69.23%. Positive dynamics were noted in the indicators of myotonometry of the quadriceps muscle and measurement of the perimeter of the knee joint. Conclusions. The program of physical rehabilitation of patients after the anterior cruciate ligament reconstruction under arthroscopic control, which was built taking into account the phase of the clinical course of the postoperative period, has been developed and offered positive results in clinical practice. The effectiveness of the program was shown by the improvement of such indicators as: decrease in intensity of pain syndrome in the early postoperative period, increase in the range of motion in the knee joint, faster restoration of the tone of the quadriceps muscle of the thighs of patients of the experimental group as opposed to the control group